1994
DOI: 10.1111/j.1432-1033.1994.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Analysis of a Serine Proteinase from Streptomyces fradiae at 0.16‐nm Resolution and Molecular Modeling of an Acidic‐amino‐acid‐specific Proteinase

Abstract: We have determined the three-dimensional structure of a proteinase from Streptomyces fradiae ATCC 14544 (SFase-2) at 0.16-nm resolution. SFase-2, a typical serine proteinase, has broad substrate specificity. The characterization and crystallographic analysis of this enzyme have been reported previously [Kitadokoro, K., Tsuzuki, H., Nakamura, E., Sato, T. & Teraoka, H. (1994) Eur: J. Biochem. 220,[55][56][57][58][59][60][61]. In the present study, data were collected to approximately 0.16-nm resolution on a Rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…According to X-ray crystallography data, their tertiary structure seems to be related to that common for chymotrypsin family [11]. It was suggested that an unusual array of three histidine residues in Streptomyces griseus protease is responsible for its specific interaction with y-carboxylate of the substrate glutamyl residue [12]; albeit, no homologous, His residues were detected in other glutamyl endopeptidases.…”
Section: Introductionmentioning
confidence: 99%
“…According to X-ray crystallography data, their tertiary structure seems to be related to that common for chymotrypsin family [11]. It was suggested that an unusual array of three histidine residues in Streptomyces griseus protease is responsible for its specific interaction with y-carboxylate of the substrate glutamyl residue [12]; albeit, no homologous, His residues were detected in other glutamyl endopeptidases.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, there are several different types of elastases, including chymotrypsin-like elastase family member 1 in the pancreas (CELA1), neutrophil elastase and macrophage metalloprotease [5,9,10]. Elastolytic activities have also been found in some microorganisms, including Pseudomonas, Clostridium, Vibrio, Aeromonas, Bacillus, Streptomyces and Aspergillus [7,8,[11][12][13][14][15][16][17][18][19][20]. The elastases produced by Pseudomonas aeruginosa [11], Clostridium histolyticum [12], Vibrio cholera [21], Vibrio vulnificus [13], Aeromonas hydrophila [14] and Aspergillus fumigatus [7] are metalloproteases, which may play an important role in helping bacterium invasiveness and establishment of infection [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The elastases produced by Pseudomonas aeruginosa [11], Clostridium histolyticum [12], Vibrio cholera [21], Vibrio vulnificus [13], Aeromonas hydrophila [14] and Aspergillus fumigatus [7] are metalloproteases, which may play an important role in helping bacterium invasiveness and establishment of infection [7,[12][13][14]. The elastases from Bacillus and Streptomyces species are serine proteases [15][16][17][18][19][20]. Tsai et al have reported that Bacillus subtilis produces an alkaline elastase (subtilisin YaB), which has high elastolytic activity and belongs to the subtilisin subfamily [15,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes have been purified to homogeneity and extensively studied. For some enzymes, such as those from Staphylococcus epidermidis, Staphylococcus aureus, Streptomyces fradiae, Streptomyces griseus, Bacillus licheniformis, Bacillus subtilis, Bacillus intermedius the corresponding genes have been cloned and the enzymes' tertiary structures have been solved (Drapeau, 1978;Svendsen et al, 1991;Barbosa et al, 1993;Neinaber et al, 1993;Kitadokoro et al, 1994;Rebrikov et al, 1999;Ohara-Nemoto et al, 2002;Mejers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%